Seasonal Phytochemical Variation and Antifungal Evaluation of Different Parts of Epidendrum Mosenii - Rosa, Patrícia Walter (2008)
Epidendrum mosenii is a Brazilian medicinal plant, traditionally used to treat infections and pains. This study reports on the chemical composition and microbiological properties of different parts and in different seasons of this plant. Results demonstrate that 4,3’,5’-trihydroxy-3-methoxy-dihydrostilbene (1), 4,5-dihydroxy-3,3-dimethoxy-dihydrostilbene (2) and pholidotin (3) were mainly present in the roots in all seasons, and the yield of mass extract increased their recovery in other parts, such as the stem and leaves for compounds (2) and (3), in summer and winter, respectively. The antifungal results indicate that compounds (1) and (2) have interesting activity against Cryptococcus neoformans, Microsporum gypseum, Trychophyton rubrum and Trychophyton mentagrophytes with MIC values between 62.5 and 125 μg/mL. Taken together, these results strongly suggest that the antifungal properties of E. mosenii are related, at least in part, to the presence of dihydrostilbenes 1 and 2, and this is useful for quality control of phytopreparations based on this plant, justifying the popular use of this plant to treat infections.